2021
DOI: 10.1177/2050313x211032398
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis of the lunate secondary to perilunate fracture dislocation: Case report and review of the literature

Abstract: This is a 39-year-old male, fell from a bike, left wrist with trans-styloid perilunate fracture dislocation that underwent open reduction internal fixation, 20 months after surgery the patient developed avascular necrosis of the lunate, final wrist fusion was performed secondary to the arthritic changes on the wrist. Anatomic dissection was performed and vascularity of the lunate was identified, its origin is from the volar palmar arch, when dislocated palmarly and more than 90 degrees the vessel is still inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…While transient vascular impairment to the lunate occurs after dorsal PLD, perilunate fracture–dislocation (PLFD), or volar lunate dislocation (LD); however, subsequent development of Kienböck disease is rare. 12 13 14 15 16 17 18 19 23 24 25 26 27 28…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While transient vascular impairment to the lunate occurs after dorsal PLD, perilunate fracture–dislocation (PLFD), or volar lunate dislocation (LD); however, subsequent development of Kienböck disease is rare. 12 13 14 15 16 17 18 19 23 24 25 26 27 28…”
Section: Resultsmentioning
confidence: 99%
“…15 The cumulative data from 23 articles, which included a total of 518 patients with PLD and PLFD, revealed that Kienböck disease was seen in 17 individuals, accounting for 3% of the total. 16…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations